Disturbance legacy of a 100-year flood event: large wood accelerates plant diversity resilience on gravel-bed rivers. (1st September 2022) - Uchida, Kei; Okazaki, Azumi; Akasaka, Takumi; Negishi, Junjiro N.; Nakamura, Futoshi
Abstract: Understanding biodiversity resilience after a major disturbance is a key issue in basic and applied science. Plant diversity in gravel-bed rivers is affected by flood events, which are one of the most effective disturbance agents in the flow regime, affecting species distribution, and ecosystem dynamics. Although disturbance plays a critical role in community assembly mechanisms, how plant diversity recovers after a severe disturbance, such as a 100-year flood event remains unknown. The present study examined how the disturbance legacy of large wood in gravel-bed river ecosystems contributes to the resilience of plant diversity. The present study demonstrated that the resilience of plant species in disturbance legacy sites, namely deposited large wood sites, was higher than that in open habitat sites. Indicator species analysis revealed that perennial plants were the most important indicator species of disturbance legacy sites. These results suggest that perennial species richness contributes to the resilience of high plant diversity across the disturbance legacy sites in this region. After major flood events, land managers often remove large wood and debris jams to avoid secondary disasters, such as embankment collapse. However, we suggest that large wood should be retained on the gravel beds to aid the recovery of biodiversity and ecosystems. Furthermore, understanding the relationships between disturbance legacies and ecosystem resilience can contribute to the formulation of strategies for sustainable ecosystem management and biodiversity conservation in the future. Highlights: Understanding biodiversity resilience after major floods is a key issue in gravel-bed rivers. How plant diversity recovers after a 100-year flood event remains unknown. The resilience of plant species diversity in large wood sites was higher than in open habitat sites. Perennial species contributes to resilience after a major flood event. Large woods should be retained on gravel beds to aid the recovery of biodiversity.